Vplyv 14 dní trvajúcej pravidelnej telesnej záťaže na koncentrácie tried a podtried lipoproteínových partikúl u mladých probandov so sedavým spôsobom života - Sabaka, P; Dukát, A; Oravec, S; Mistríková, L; Baláž, D; Bendžala, M; Gašpar, L (Vnitrni lekarstvi, 2013)
Recommendations from the cardiological professional companies working in the area of primary prevention of cardiovascular diseases put an emphasis on regular aerobic physical activity. Its positive effect on both cardiovascular and overall mortality has repea-tedly been proven by the observations of prospective and cross sectional epidemiological studies. One of the possible explanations of this positive effect is a change in the concentration of lipoprotein classes and their subclasses, which is expressed as a change in their average size. In a group of young healthy men and women with a sedentary lifestyle we observed the effect of medium intensive physical exercise in the form of a 30- minute slow run per day lasting for 14 days. The concentration of lipoprotein classes and subclasses were determined through the method of a linear electrophoresis in polyacrylamide gel. In the observed group we found a statistically significant decrease of VLDL, large IDL particles, medium sized LDL, small dense LDL, and medium sized HDL particles. In the light of current knowledge all these lipoprotein particles are deemed as atherogenic. Thus, as little as 14 days of regular exercising has a positive effect on the concentration of plasmatic lipoproteins, and emphasises the role of regular physical activity in the primary prevention of cardiovascular diseases.
Keywords: Young Adult; Sedentary Behavior; Lipoproteins; Adult; Male; lidé; dospělí; mužské pohlaví; ženské pohlaví; cvičení; sedavý životní styl; Female; Humans; mladý dospělý; Exercise; lipoproteiny